Position and ranking influence in padel: somatic anxiety and self-confidence increase in competition for left-side and higher-ranked players when compared to pressure training - Conde-Ripoll, Rafael; Escudero-Tena, Adrián; Bustamante-Sánchez, Álvaro (Frontiers in Psychology, 2024)
This study aimed to analyze the differences in the precompetitive anxiety and self-confidence according to the side of play, the ranking and the match outcome, under different competitive scenarios, in high level men´s padel players from Finland who trained under pressure prior to the competition. 10 men´s padel players (28.60(4.17) years old) from the highest category participated in the research. The CSAI-2R (Competitive State Anxiety Inventory-2 Revised) and STAI-S (State-Trait Anxiety Inventory -State) questionnaires were used and descriptive and inferential analyzes were performed, including Mann-Whitney´s U tests. The findings illuminate that, across the player spectrum, somatic anxiety and self-confidence levels are higher before competition compared to training matches. This trend holds true for backhand-side, higher-ranked and match winning players. Even lower-ranked players exhibit heightened self-confidence preceding competitions. These insights offer valuable considerations for players, coaches, and sports psychologists, fostering a deeper understanding of the intricate interplay between pressure training, competition, and the athlete's psychological landscape.